The Semantics of Nouns Derived From Gradable Adjectives - Nicolas, David (Proceedings of Sinn und Bedeutung, 2019)
What semantics should we attribute to nouns like wisdom and generosity, which are derived from gradable adjectives? We show that, from a morphosyntactic standpoint, these nouns are mass nouns. This leads us to consider and answer the following questions. How are these nouns interpreted in their various uses? What formal representations may one associate with their interpretations? How do these depend on the semantics of the adjective? And where lies the semantic unity of nouns like wisdom and generosity with the more familiar concrete mass nouns, like wine and furniture?